2019
DOI: 10.11606/s1518-8787.2019053001568
|View full text |Cite
|
Sign up to set email alerts
|

How important is school environment in explaining individual variance of health behaviors?

Abstract: We analyzed data from the National School-based Health Survey (PeNSE) carried out in Brazil in 2015 (n = 102,072 adolescents) to estimate how much of the individual variance in the prevalence of health behaviors is attributable to the school level. Multilevel logistic regression models were calculated to estimate the variance partitional coefficient (VPC) of the use of drugs, intake of unhealthy food, leisure physical activity and weight-related behaviors. The between-schools variance was significant in all te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Um estudo, também realizado com dados da PeNSE de 2015, ao estimar quanto da variação individual na prevalência de comportamentos de saúde é atribuível ao nível escolar, mostrou a importância do contexto escolar na saúde do adolescente e destacou que as intervenções no ambiente escolar podem ser eficazes para promover comportamentos saudáveis 36 . Logo, parece plausível afirmar que regulamentar e restringir o que é vendido nas escolas pode melhorar a alimentação dos adolescentes.…”
Section: Modelos Brutosunclassified
“…Um estudo, também realizado com dados da PeNSE de 2015, ao estimar quanto da variação individual na prevalência de comportamentos de saúde é atribuível ao nível escolar, mostrou a importância do contexto escolar na saúde do adolescente e destacou que as intervenções no ambiente escolar podem ser eficazes para promover comportamentos saudáveis 36 . Logo, parece plausível afirmar que regulamentar e restringir o que é vendido nas escolas pode melhorar a alimentação dos adolescentes.…”
Section: Modelos Brutosunclassified
“…In addition, the adjustments were made for relevant confounders that are not usually controlled in studies on diet and mental health in adolescence, such as whether they study in a public or private school, in urban or rural areas, physical activity, whether they live and have meals with their parents, the number of close friends, self-perceived body image, and whether they had been bullied at school. Considering the importance of these school and family contextual aspects for eating behavior [30,[47][48][49][50][51] and mental health [3,52], our study takes the knowledge a step further by demonstrating that the relationship between UPF consumption and poor mental health is maintained regardless of these factors.…”
Section: Discussionmentioning
confidence: 87%
“…In a study by Chac ón-Cuberos et al (52) , adolescents who followed healthy eating habits showed academic benefits, such as better organisational habits, critical thinking, effort and study habits. Boing et al (61) highlight that school environment interventions may be effective for promoting healthy behaviours and reinforce the importance of the school context on adolescent health. School can facilitate the engagement in healthy behaviour by offering and stimulating opportunities to be healthy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…offer healthy options in the cafeteria, etc) and by promoting barriers to unsafe/unhealthy behaviour (e.g. not selling energy-dense foods in the cafeteria) (61,62) . Aarestrup AK et al (63) found that schools that promote barriers to unsafe/unhealthy behaviours, while having teachers and students who value that policy, show higher rates of programme implementation and acceptance for change.…”
Section: Discussionmentioning
confidence: 99%